THE SYNTACTIC STATUS OF INTRODUCTORY PARTS OF SENTENCES IN NON-RELATED LANGUAGES(ENGLISH AND UZBEK) (Лучшие интеллектуальные исследования, 2025)
Annotation: This arlicle outlines the syntactic status and relationship of introductory parts with other parts of sentences, and their communicative-pragmatic types in English and Uzbek. Introductory components are usually known as a part of the sentence that is not dependent on the other parts of that sentence. However, at the same time introductory elements gain the property of an individual member of sentences, because as part of the sentences they are semantically and syntactically contact with this sentence, have certain relationships with it. And as to their communicative-pragmatic aspects, introductory elements are classified into several types . In this article, we try to analyze those issues and work out possible conclusions.